The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1128/jvi.00827-07
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Gene Expression Is Silenced by Daxx-Mediated Intrinsic Immune Defense in Model Latent Infections Established In Vitro

Abstract: In addition to productive lytic infections, herpesviruses such as human cytomegalovirus (HCMV) establish a reservoir of latently infected cells that permit lifelong colonization of the host. When latency is established, the viral immediate-early (IE) genes that initiate the lytic replication cycle are not expressed. HCMV IE gene expression at the start of a lytic infection is facilitated by the viral pp71 protein, which is delivered to cells by infectious viral particles. pp71 neutralizes the Daxx-mediated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
211
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(226 citation statements)
references
References 91 publications
(127 reference statements)
14
211
0
1
Order By: Relevance
“…In differentiated cells, pp71 translocates to the nucleus after virus entry and associates with nuclear domain 10 (ND10)-structures, where it prevents histone deacetylase (HDAC)-mediated IE gene silencing by neutralizing the ATRX-Daxx repressor complex (3,4). In contrast, in undifferentiated cells, like CD34+ hematopoietic progenitors or embryonic cell lines, pp71 remains cytoplasmic and consequently a quiescent or latent mode of infection is favored (5,6).…”
mentioning
confidence: 99%
“…In differentiated cells, pp71 translocates to the nucleus after virus entry and associates with nuclear domain 10 (ND10)-structures, where it prevents histone deacetylase (HDAC)-mediated IE gene silencing by neutralizing the ATRX-Daxx repressor complex (3,4). In contrast, in undifferentiated cells, like CD34+ hematopoietic progenitors or embryonic cell lines, pp71 remains cytoplasmic and consequently a quiescent or latent mode of infection is favored (5,6).…”
mentioning
confidence: 99%
“…A similar chromatin structure is also observed on viral genomes when HCMV infects NT2 and THP-1 cells in vitro, two model systems that are used to study quiescent HCMV infections [86][87][88]. Infections in NT2 and THP-1 cells are referred to as quiescent (or latent like) because treatments that can reactivate expression from the silenced viral genomes in these cells (if they exist) have not yet been identified [89][90][91][92]. Additionally, in lytically-infected fibroblasts prior to pp71-mediated degradation of Daxx, HCMV genomes adopt a chromatin structure indistinguishable from that observed in CD34 + and NT2 cells [45].…”
Section: While They Inhibit Lytic Replication Do Pml-nb Proteins Facmentioning
confidence: 92%
“…The mechanism by which the repressive chromatin structure is established on latent viral genomes in CD34 + cells has yet to be analyzed, but it is now evident that PML-NB proteins and HDACs contribute to this process at the start of lytic and quiescent HCMV infections. Chemical HDAC inhibitors permit IE gene expression in NT2 and THP-1 cells [87,90,92,93], indicating that HDACs play a role in transcriptional repression during HCMV quiescence. A study from our laboratory found that the knockdown of Daxx prior to HCMV infection also permits IE gene expression in NT2 and THP-1 cells [92].…”
Section: While They Inhibit Lytic Replication Do Pml-nb Proteins Facmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is unclear if hDaxx has a major role in repression of HCMV gene transcription during latency. In the embryonic carcinoma cell line NT2D1, which can recapitulate the differentiation-dependent regulation of IE gene expression observed during latency, repression of IE gene expression has been reported in the presence (Saffert & Kalejta, 2007) and absence (Groves & Sinclair, 2007) of hDaxx in undifferentiated NT2D1 cells. This may be due to differences in the virus strains used in each study.…”
Section: Further Questions and Future Perspectivesmentioning
confidence: 99%